2016
DOI: 10.1371/journal.pone.0155241
|View full text |Cite
|
Sign up to set email alerts
|

Recent Shift in Climate Relationship Enables Prediction of the Timing of Bird Breeding

Abstract: Large-scale climate processes influence many aspects of ecology including breeding phenology, reproductive success and survival across a wide range of taxa. Some effects are direct, for example, in temperate-zone birds, ambient temperature is an important cue enabling breeding effort to coincide with maximum food availability, and earlier breeding in response to warmer springs has been documented in many species. In other cases, time-lags of up to several years in ecological responses have been reported, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In a study of tree swallows in California, Rose [50] found that average daily wind speed had a significant negative effect on the rate that adult tree swallows fed their young. Wet, cold, and windy conditions have also been seen to cause delays in egg laying and incubation in other tree swallow populations [48,49] as well as in other birds ( [8,10], but see [7]). These studies, plus the concordance of climate effects at our two study sites, suggests that the effect of wind observed in this study is not spurious, but reflects an important aspect of climate for this species that is rarely considered in analyses of climate change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study of tree swallows in California, Rose [50] found that average daily wind speed had a significant negative effect on the rate that adult tree swallows fed their young. Wet, cold, and windy conditions have also been seen to cause delays in egg laying and incubation in other tree swallow populations [48,49] as well as in other birds ( [8,10], but see [7]). These studies, plus the concordance of climate effects at our two study sites, suggests that the effect of wind observed in this study is not spurious, but reflects an important aspect of climate for this species that is rarely considered in analyses of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change is a global phenomenon with well-documented effects, including increasing temperatures as well as changes in precipitation, humidity, snow pack depth and duration, storm frequency, and wind speed [1][2][3][4]. There is substantial evidence that climate change is causing or will cause range and phenology shifts in individual species and will alter the structure and composition of entire communities [5][6][7][8][9][10][11][12][13][14]. Determining what aspects of climate are driving these changes is challenging because of annual climate variation and the correlated shifts in multiple aspects of climate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In seasonally breeding vertebrates, reproductive events are timed so that food availability is highest when nutritional demands of breeding are highest (Hau, 2001;Hinsley et al, 2016;Nager & van Noordwijk, 1995;Van Noordwijk et al, 1995). Increasing food availability directly triggers breeding in some species (Hau, 2001) but many use indirect cues.…”
Section: Introductionmentioning
confidence: 99%